Gastro‐esophageal reflux and antisecretory drugs use among patients with chronic autoimmune atrophic gastritis: a study with pH‐impedance monitoring. Issue 2 (15th November 2015) - Tenca, A.; Massironi, S.; Pugliese, D.; Consonni, D.; Mauro, A.; Cavalcoli, F.; Franchina, M.; Spampatti, M.; Conte, D.; Penagini, R.
Abstract: Background: Patients with chronic autoimmune atrophic gastritis (CAAG) often refer digestive symptoms and are prescribed antisecretory medications. Aims were to investigate: (i) gastro‐esophageal reflux (GER), (ii) psychopathological profile, (iii) frequency of use and clinical benefit of antisecretory drugs. Methods: Prospective observational study on 41 CAAG patients who underwent: 24 h multichannel intra‐luminal impedance‐pH (MII‐pH) monitoring off‐therapy, standardized medical interview and psychological questionnaire (i.e., SCL‐90R). The medical interview was repeated at least 1 month after MII‐pH in patients who were using antisecretory drugs. Statistical analysis was performed calculating median (10th–90th percentiles) and risk ratios (RR) with 95% confidence interval. Key Results: Median intra‐gastric pH was 6.2 (4.6–7.0). One patient had acid reflux (AC) associated with symptoms, five had increased total reflux number and four had symptoms associated to non‐acid reflux (NA) (patients referred as 'GER positive'). Using patients 'GER negative' with normal SCL‐90R as reference, the RR of being symptomatic in patients GER positive was 2.1 (1.1–4.1) if SCL‐90R was normal and 0.9 (0.5–1.7) if it was altered (difference in RR significant being p = 0.04). Seventeen/28 (61%) symptomatic patients were on antisecretory drugs, which were stopped in 16 of them according to results of MII‐pH and clinical evaluation after 574 days (48–796) showed that symptoms were unchanged. Conclusions & Inferences: In patients with CAAG (i) AC reflux rarely occurred whereas increased NA reflux was not infrequent both being related to symptoms in some patients, (ii) psychopathological profile has a role in symptoms' occurrence, (iii) antisecretory drugs were generally inappropriately used and clinically ineffective. Abstract : (1) Study investigating (i) gastro‐esophageal reflux, (ii) psychological profile, (iii) antisecretory drugs use in patients with chronic autoimmune atrophic gastritis. (2) Reflux (acid and non‐acid) may be related to symptoms in some patients and psychological profile may play a role in symptoms' occurrence. (3) Antisecretory drugs were generally inappropriately prescribed and ineffective.